Cyromazine affects the ovarian germ cells of Drosophila via the ecdysone signaling pathway - Khalid, Muhammad Zaryab; Sun, Zhipeng; Zhang, Jing; Zhang, Shijie; Zhong, Guohua (Frontiers in Physiology, 2022)
Cyromazine, an insect growth regulator, has been extensively used against the insect pests of livestock and households. Previously, it was observed that the continuous selection of cyromazine from the larval to the adult stage decreased the number of germline stem cells (GSCs) and cystoblasts (CBs) in the adult ovary. In addition, in this study, we observed that the number of primordial germ cells (PGCs) was also decreased in the larval ovary after treatment with cyromazine. However, the mechanism by which it affects the germ cells is yet to be explored. Consequently, to deeply investigate the effects of cyromazine on the germ cells, we performed tissue-specific RNA sequencing. Bioinformatics analysis revealed that the ecdysone signaling pathway was significantly influenced under cyromazine stress. Based on that, we screened and selected 14 ecdysone signaling responsive genes and silenced their expression in the germ cells only. Results of that showed a considerable reduction in the number of germ cells. Furthermore, we mixed exogenous 20E with the cyromazine-containing diet to rescue the ecdysone signaling. Our results supported that the application of exogenous 20E significantly rescued the germ cells in the transgenic lines. Therefore, this implies that the cyromazine decreased the number of germ cells by affecting the ecdysone signaling pathway.